SPECIFIC ASPECTS OF PROGNOSIS AND TREATMENT OF ELDERLY PATIENTS WITH LARGE B-CELL LYMPHOMA - Markovic, Olivera; Bukurecki, Ilija; Stanisavljevic, Natasa; Divac, Anica; Todorovic, Zoran; Cvetkovic, Zorica (Medical Research, 2024)
Large B-cell lymphoma (LBCL) is the most common type of non-Hodgkin lymphoma in the general population, constituting 40-50% of all NHL cases, and over 60% of lymphoma cases in the population of patients over 65 years. Given their increasing life expectancy, the prevalence of this lymphoma type is expected to grow in the coming years. Treating those patients is a significant challenge due to numerous factors that complicate treatment and worsen the disease's outcome. Elderly patients are often foundwith comorbid conditions, weakened organ function, altered drug metabolism, and reduced hematopoietic capacity for bone marrow recovery, making them less tolerant to chemotherapy. A poorer prognosis is attributed to a higher frequency of the non-GCB subtype and histologically unfavorable types of LBCL, such as EBV-positive LBCL, High-grade B-cell lymphoma(HGBL), and plasmablastic lymphoma, as well as extranodal localizations associated with worse outcomes. Treating elderly patients is complex because they represent a highly heterogeneous population with significant variations in health status, comorbid conditions, and expected lifespans. Therefore, when it comes to elderly patients, a comprehensive geriatric assessment is necessary, including the determination of a comorbidity index to differentiate between those in good general condition (fit), those in poor general condition (frail), and those in between. The goal of treatment can be recovery, extension of life, or symptom control. The standard therapy for elderly patients with good general condition and advanced disease is R-CHOP, while for patients with comorbidities and poor general condition, reduced protocols with or without anthracyclines are considered. Previously, elderly patients with relapsed or refractory LBCL faceda very poor prognosis due to limited treatment options. However, the success of treating elderly patients with R/R LBCL has improved in recent years due to the introduction of new drugs (polatuzumab, tafasitamab, bispecific antibodies, and CAR-T cells) that can be used in older individuals.
Keywords: large B cell lymphoma, elderly, prognosis, therapy